Adequacy of the sodium concentration in mass consumption baked goods marketed in Paraguay (2014 – 2021) - Galeano Miers, Marcelo Javier; Acosta Escobar, José; Morínigo Isla, Geraldine; Bonzi Arévalos, Carolina; Ovelar Fernández, Elsi Carolina; González Cañete, Natalia Elizabeth (Medicina Clínica y Social, 2024)
Introduction: Within the framework of the implementation of public health strategies aimed at stopping the advance of chronic non-communicable diseases of nutritional origin in Paraguay, the salt content (sodium chloride) in baked goods has been regulated. The Instituto Nacional de Alimentación y Nutrición (INAN, National Institute of Food and Nutrition) monitors the sodium content in baked goods in the national territory. Objective: Determine the adequacy of the sodium content in mass-consumption baked goods, manufactured and marketed in Paraguay, from 2014 to 2021. Methodology: Observational, descriptive, retrospective study. Data obtained as part of the surveillance carried out by the INAN on mass consumption baked goods prepared and marketed at the national level were evaluated. Sodium was analyzed using the AOAC 985.35 procedure, and adequate values were considered when the sodium concentration was ? 600 mg/Na per 100 g of product, according to S.G. Resolution No. 792/2015. Results: 527 samples of mass consumption baked goods were analyzed from outlets, from 16 health regions, and from commercial industries (1.1%), supermarkets (87.2%) and bakeries (11.7%). During the years 2017, 2018 and 2021, the medians and averages of sodium far exceeded the values established as adequate. There were significant differences in the percentage of samples with adequate and inadequate values according to the year of monitoring. The samples of “palitos, coquitos and rosquitas” presented a significantly higher amount of sodium in relation to what was found in Felipe bread, “galletas”, and other baked goods (p= < 0.05). Discussion: Surveillance and compliance by companies with S.G. Resolution No. 792/2015 is essential to avoid excess sodium in mass-consumption baked goods. Continuing monitoring is required to ensure compliance with current legislation